Echocardiographic evaluation of the right ventricular dimension and systolic function in dogs with pulmonary hypertension. (14th September 2018) - Vezzosi, Tommaso; Domenech, Oriol; Costa, Giulia; Marchesotti, Federica; Venco, Luigi; Zini, Eric; del Palacio, Maria Josefa Fernández; Tognetti, Rosalba
Abstract : Background: Right ventricular (RV) enlargement and dysfunction are associated with prognosis in humans with pulmonary hypertension (PH). Hypothesis/Objectives: To assess RV size and systolic function in dogs with PH and to determine if they are associated with disease severity and right‐sided congestive heart failure (R‐CHF). Animals: 89 dogs with PH and 74 healthy dogs. Methods: Prospective observational study. PH was classified according to the tricuspid regurgitation pressure gradient. RV end‐diastolic area (RVEDA) index was calculated as RVEDA divided by body surface area. RV systolic function was assessed with the tricuspid annular plane systolic excursion (TAPSE) and the RV fractional area change (FAC) normalized for body weight (TAPSEn and FACn, respectively). Results: RVEDA index was higher in dogs with moderate PH (10.8 cm 2 /m 2 ; range, 6.2‐14.4 cm 2 /m 2 ) and severe PH (12.4 cm 2 /m 2 ; range, 7.7‐21.4 cm 2 /m 2 ) than in those with mild PH (8.4 cm 2 /m 2 ; range, 4.8‐11.6 cm 2 /m 2 ) and control dogs (8.5 cm 2 /m 2 ; range, 2.8‐11.6 cm 2 /m 2 ; P < .001). RVEDA index was significantly higher in dogs with R‐CHF (13.7 cm 2 /m 2 ; range, 11.0‐21.4 cm 2 /m 2 ) than in dogs without R‐CHF (9.4 cm 2 /m 2 ; range, 4.8‐17.1 cm 2 /m 2 ; P < .001). The severity of tricuspid regurgitation (TR) was the only independent predictor of the RVEDA index ( P < .001). TAPSEn and FACn were not significantly different among varying degrees of PH severity and between dogs with and without R‐CHF. Conclusions and Clinical Importance: The RVEDA index can be used to evaluate RV size in dogs. It can provide additional information in dogs with PH and predict R‐CHF. Severity of TR is the main determinant of RV enlargement in dogs with PH.